Causes, management and complications of severe adult dehydration in the emergency room - Ghafouri, Abdulrahman Mohammad; Arkoubi, Shurouq Hamzah; Al-Amri, Talal Maqboul; Alshamari, Afaf Matar; Alqahtani, Mohammed Ali; Alyami, Zainalaabdeen Sayyar; Alnemer, Eiman Mohammad; Almujayrishi, Ahmed Musallam; Najdi, Najdi Ibrahem; Althobaiti, Nawwaf Jamaan; Lamfon, Hanan Yahia; Alyahya, Rayyan Abdullah; et al. (International Journal Of Community Medicine And Public Health, 2021)
This literature review aims to highlight the possible causes, complications, and management of this event from previously published studies discussing dehydration in critically-ill patients admitted to the emergency room (ER). In general, the administration of fluids has been used in the ER for critically-ill patients for many purposes. These include the optimization and adjustment of body fluids and electrolytes, increase renal protection against contrast, enhance uric acid, globins, caloric intake, and as an adjuvant to ameliorate the potentiality of certain medications or to dilute them. Many etiologies have been accused to cause dehydration in critically-ill patients. These include the fasting strategy that patients are obliged to whenever undergoing a surgical operation. Kidney, heart, and liver injuries have also been associated with patients’ dehydration. Old age and the presence of other co-morbidities diabetes insipidus and uncontrolled diabetes can also aggravate the condition. Mental affection is the main complication that patients with severe dehydration might complain about. Other complications might include aggravation of heart failure, and skin diseases, and deterioration of the kidney functions and other cellular processes that require adequate nourishment for their daily normal functions. Mortality is also a serious common complication, especially within elderly patients. Although the management of dehydration can be easily achieved by fluid administration, fluid overload can aggravate the underlying complications and develop others. Therefore, the main challenge here would be to frequently monitor patients during fluid administration and resuscitation to prevent this side effect.